Radio Frequency Identification (RFID) Implementation for Improving IBS Components Management at Manufacturer Storage Area - May Ying, Wee; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2021)
Radio frequency identification (RFID) has been broadly applied in various industry but in construction industry the current technology used to identify the components are still barcodes technology. The major issue found in precast manufacturer were the difficulties in locating precast pieces at storage area that stored thousands of different component. With the current barcode technology, it required a line of sight to access each code. Hence, finding pieces becomes very difficult. The objectives of this research are to study the potential, identify the challenges and to determine the improvement ways of radio frequency identification (RFID) implementation for improving IBS components management at manufacturer storage area. To achieve the objectives of this research, quantitative method was adopted by using questionnaire. Questionnaires were distributed to IBS manufacturers in Selangor area to obtain data. The research findings revealed that provide real time tracking of IBS components, provide real time identification of IBS components and reduce manual interference in the management process are top three key potential influencing implementation of RFID technology by the IBS manufacturer. The research also identifies high cost for active tag implementation as key challenges that encountered by IBS manufacturer and main improvement ways of RFID technology implementation is technology promotion by top management. In conclusion, this research can assist the IBS manufacturer who wish to implement RFID technology in IBS component management.